Implicancias del Brexit en la Unión Europea - Prado, Josefina del (2018)
June 23, 2016, will be a day difficult to forget, mainly in Europe. Should the United Kingdom remain part of the European Union (EU) or not?, was the question posed in the historic referendum and the majority, with a very little margin, voted in favor of leaving the EU. This is how the United Kingdom became the first country that decided to leave the European Union, where it remained for more than four decades, dealing an unprecedented blow to an emblematic integration process worldwide. In what it seems an irreversible process, the United Kingdom began on March 29, 2017, the formal process to leave the European Union (EU), activating Article 50 of the Treaty of Lisbon that provides a mechanism for the voluntary and unilateral withdrawal of a country of the European Union. The result of the referendum and the express mention of the recovery of independence and sovereignty by the British Prime Minister Theresa May reflect the primacy of Eurosceptic or Europhobic positions on the island against the pro-Europeans. In the following lines, we will reflect on the underlying forces of the European integration process, its main milestones, to analyze the role of the United Kingdom in it and the impact of the withdrawal of the UR to the EU.